Performance and Reliability Analysis of Double Boost Converter Fed Renewable PV System - V. Lakshmi Devi; K. Kumar; R. Karpaga Priya; Mohd Asif Shah (Journal of Engineering)
The article gives the performance and reliability analysis of renewable PV systems fed with a double boost converter. For analyzing the PV system performance and reliability, a 660 W PV system is considered and a double boost converter with the PSO MPPT method is implemented by adding a secondary path to the conventional boost converter, which shares the input current and reduces the current ripples in the system. For a detailed analysis of the system, different solar irradiations of 1000 W/m2, variable irradiations, and real-time solar irradiation in the area of 13039129.311N 79029109.311E on May 2022 are considered and reliability indices are presented at PV system and power electronic converter components. A MATLAB/Simulink environment is chosen for analysis of the proposed system in different conditions.